2013
DOI: 10.2466/29.30.pms.116.3.905-917
|View full text |Cite
|
Sign up to set email alerts
|

Mental Toughness of Mixed Martial Arts Athletes at Different Levels of Competition

Abstract: This study investigated whether mental toughness distinguishes mixed martial arts (MMA) athletes competing at different levels. It was theorized that higher mental toughness would separate those competing at the professional level compared to lower levels. Male MMA competitors (N = 136, M age = 27.1 yr., SD = 4.8) were categorized as amateur, semi-professional, or professional and assessed by questionnaire using the Psychological Performance Inventory-A and the Sports Mental Toughness Questionnaire. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 21 publications
3
46
0
3
Order By: Relevance
“…Of the four studies that found subcomponent MT differences among three or more groups, the two single sport studies identified differences between the highest standard and all lower standards [35,39]. Differences in the remaining two studies (multiple sports) were solely between the highest and lowest [30], the two highest and two lowest, and the two lowest competitive standard groups [8].…”
Section: Mental Toughness and Competitive Standardmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the four studies that found subcomponent MT differences among three or more groups, the two single sport studies identified differences between the highest standard and all lower standards [35,39]. Differences in the remaining two studies (multiple sports) were solely between the highest and lowest [30], the two highest and two lowest, and the two lowest competitive standard groups [8].…”
Section: Mental Toughness and Competitive Standardmentioning
confidence: 99%
“…However, the terminology and groupings used by researchers tended to differ across many of the studies. For instance, selected researchers used country, provincial, and county to distinguish athletes [34], whereas athletes were categorized according to professional status level, such as professional, semi-professional, and amateur [35]. Some combined competitive standards (e.g., club and national level players) [26] that others separated [36].…”
Section: Sample Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological factors were also able to increase the efficiency of different muscular movements in specific karate tests (20). However, associations between physical and psychological analysis are scarce in kickboxing, which is required to support the hypothesized issues underlying mental toughness, especially, concerning key elements that can help to develop physical capabilities and, at the same time, improve emotional conditions during the competitive challenges (16, 17). …”
Section: Introductionmentioning
confidence: 99%
“…A confiança é importante, no sentido de atletas geralmente assumirem grandes riscos físicos por confiarem em suas habilidades atléticas e devido à vontade de superar desafios 38 . As características dessa modalidade requerem quantidade superior de recursos para lidar com as crescentes demandas do ambiente 39 . O fator treinabilidade (Tabelas 1, 3 e 5) também se constituiu como essencial para atletas desta modalidade, uma vez que devem estar dispostos a aprender no seu treinamento.…”
Section: Discussionunclassified